Use of secondary somatic embryos promotes genetic fidelity in cryopreservation of cocoa (Theobroma cacao L.) - Fang, Jong-Yi; Wetten, Andy; Adu-Gyamfi, Raphael; Wilkinson, Mike; Rodriguez-Lopez, Carlos (MTT Agrifood Research Finland, 2009)
The inability to conserve cocoa (Theobroma cacao L.) germplasm via seed storage and the vulnerability of field collections make the establishment of cryopreserved genebanks for the crop a priority. An effective encapsulation-dehydration based cryopreservation system has been developed for cocoa but because the somatic embryos used for freezing arise after a protracted period of callus culture there is concern about maintenance of genetic fidelity during the process. Microsatellite markers for seven of the 10 cocoa linkage groups were used to screen a population of 189 primary somatic embryo-derived emblings and the 43 secondary somatic embryos they gave rise to. Of the primary somatic embryos, 38.1% exhibited polymorphic microsatellite profiles while for secondary somatic embryos the frequency was 23.3%. The same microsatellite markers used to screen another population of 44 secondary somatic embryos cryopreserved through encapsulation-dehydration revealed no polymorphisms. Scanning electron microscopy showed the secondary somatic embryos were derived from cotyledonary epidermal cells rather than callus. The influence of embryo ontogeny on somaclonal variation is discussed.
Keywords: Pu; Ka; Cocoa; Theobroma cacao; somatic embryogenesis; somaclonal variation; cryopreservation